Distributed prescribed-time attitude coordination for multiple spacecraft with actuator saturation under directed graph - Xu, Chuang (2022)
This article studies the distributed prescribed-time coordination problem for the attitude system of multiple spacecraft subject to actuator saturation under the communication topology containing a directed spanning tree. The prescribed-time coordination requires that every spacecraft in a formation reaches an agreement state in a preset time. This preset time is set by the user and independent of any other control parameters and the initial state of spacecraft. To achieve this goal, we first design a distributed prescribed-time observer for every follower spacecraft to estimate the state of leader spacecraft. Next, a prescribed-time attitude control law is proposed by utilizing the estimated state of the leader spacecraft. In the proposed control law, an adaptive compensation law is used to compensate the input saturation. Furthermore, the prescribed-time stability of multispacecraft system subject to input saturation under the proposed scheme is analyzed in theory and simulation. The simulation results show the high reliability and effectiveness of the scheme.